Dimensional Stability and Microstructural Properties of Cements with Different C3A Contents - Kaplan, Gökhan; Öztürk, Ali̇ Uğur (Springer Science and Business Media LLC, 2019)
Concrete and reinforced-concrete structures are exposed to water loss and chemical effects which lead to dimensional changes. Used as a binding material in concrete production, cement’s physical and chemical properties play an important role in this process. Especially the C3S content and C3A content of cement influence the properties of concrete such as shrinkage and chemical resistance. In this study, cements were produced using four different clinkers with different chemical compositions. Properties such as drying shrinkage, mechanical properties, sulfate resistance (10% Na2SO4–MgSO4), and microstructure were explored up to the 365th day of the production of the cements. It was observed that cements with a higher C3A content (produced using especially the Portland cement) shrank more in the water. It was found that Cement B which shrank more in the water, shrank less when stored at room temperature. Cements with higher C3S content contribute greatly to the early age strength. Cements with higher C2S content, on the other hand, offer increased strength starting from the 90th day up to 365th day. Cement C with the lowest C3A content (3.37%) was found to be more suitable in terms of its sodium and magnesium sulfate resistance. Cements stored in sulfate proved to have increased expansion reactions generally after the 210th day. Increased C3S/C3A ratio also increases the sulfate resistance of cements. Weight loss was the case under the effect of magnesium sulfate while expansion was increased under effect sodium sulfate conditions. Thaumasite damage was observed in cement pastes stored in magnesium sulfate at 20 °C as CO2 available in the water was dissolved. Nevertheless, cement’s resistance class is more important than the C3A content when the cement is exposed to the effects of magnesium sulfate. Therefore, it is recommended for the future research to explore the limitation of C3S content in cements exposed to magnesium sulfate.
Keywords: 6. Clean water; 12. Responsible consumption